2019
DOI: 10.18502/fid.v16i4.2089
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Three Commonly Consumed Beverages on Surface Roughness of Polished and Glazed Zirconia-Reinforced Lithium Silicate Glass Ceramics

Abstract: Objectives: This study aimed to assess the effect of three commonly consumed beverages on surface roughness of polished and glazed zirconia-reinforced lithium silicate (ZLS) glass ceramics. Materials and Methods: In this experimental study, 104 rectangular specimens were cut from Vita Suprinity blocks with 2 mm thickness. After ultrasonic cleaning and firing of the specimens, they were finished and polished in two groups. Specimens in the first group were polished using a 2-step polishing kit while the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 34 publications
(16 reference statements)
4
16
0
Order By: Relevance
“…The presence of a glassy matrix may lead to the dissolution of the glass network, considering that alkaline ions (Si, Ca, and Mg) are less stable when in a glassy matrix phase than in a crystalline phase (30,31) . This is in agreement with previous studies in which the surface roughness of polished Vita Suprinity specimens increased after acid exposure (34,35) .…”
Section: Discussionsupporting
confidence: 94%
“…The presence of a glassy matrix may lead to the dissolution of the glass network, considering that alkaline ions (Si, Ca, and Mg) are less stable when in a glassy matrix phase than in a crystalline phase (30,31) . This is in agreement with previous studies in which the surface roughness of polished Vita Suprinity specimens increased after acid exposure (34,35) .…”
Section: Discussionsupporting
confidence: 94%
“…In the oral environment, dietary pH fluctuates from acidic to alkaline depending on personal dietary preferences. Research studies reported different pH levels in food, drinks, and fruits [18][19][20][21], which could initiate the potential dissolution of teeth or the corrosion of ceramic materials. Despite the buffering capacity of saliva and cleansing ability of the tongue, the oral cavity is a harsh environment for restorative dental materials.…”
Section: Introductionmentioning
confidence: 99%
“…The roughening of ceramic surfaces is detrimental to the surface integrity of the opposing enamel antagonist [23] and adversely affects the fracture strength of the restoration [24,25]. International Standards Organization (ISO) standard 6872 tests for dental ceramic chemical durability [26] and constantly immerses ceramic in 4% acetic acid at 80 • C for 16 h. However, several studies demonstrated the effect of different pH solutions on the surface degradation and corrosion of ceramic [20,21,27,28]. Firouz et al showed orange juice (pH 3.5) and cola (pH 2.4) increased the surface roughness of ceramic [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Vita Suprinity showed a rougher surface after acid exposure (19,36) , it displayed more translucency. This is maybe the result of its high glass content and lithium silicate crystals that offer the material with its superior optical characteristics (37) .…”
Section: Discussionmentioning
confidence: 99%